The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3174/ajnr.a3174
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-Weighted Imaging–Derived Collateral Flow Index is a Predictor of MCA M1 Recanalization after IV Thrombolysis

Abstract: BACKGROUND AND PURPOSE:Recent studies highlight the role of CC in preserving ischemic penumbra. Some authors suggested the quality of CC could also impact recanalization. The purpose of this study is to test this hypothesis in patients who were treated with IV thrombolysis for MCA-M1 occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Biases in patient selection for MRI were limited, since patients received protocolised serial MRI. Additionally, lesion volume and final infarct size (corresponding lesion volume on follow-up FLAIR imaging) were volumetrically characterised by blinded reviewers using standardised software 23. This study is also the first to look at risk factors for early MRI ischaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biases in patient selection for MRI were limited, since patients received protocolised serial MRI. Additionally, lesion volume and final infarct size (corresponding lesion volume on follow-up FLAIR imaging) were volumetrically characterised by blinded reviewers using standardised software 23. This study is also the first to look at risk factors for early MRI ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Shine-through DWI positive, FLAIR bright lesions that were not dark on ADC were excluded. The volumes of these selected ADC dark lesions were measured by two investigators (WA, VZ), blinded to the patient's clinical condition and outcome using Neuroscape software (Olea, La Ciotat, France) 23. Lesions were considered to be distinct if they were separated by 5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to note that although there is general agreement that the size of the core infarct is an important factor in patient outcomes, it has been suggested that there may be better predictors of outcomes such as certain perfusion measurements. [26][27][28][29] Currently, intravenous thrombolytic therapy is administered in only 1% to 7% of cases (high performing centers approach 15%-20%), with most patients ineligible because they present outside the 3-to 4.5-hour treatment window. [30][31][32][33] Proximal anterior circulation artery occlusions may respond well to intra-arterial thrombolysis and mechanical thrombectomy; however, these treatments are also typically restricted by adherence to time windows of 6 and 8 hours, respectively, from the time of stroke onset.…”
Section: Strokementioning
confidence: 99%
“…A recent study suggested that a normalized index derived from Tmax maps calculated from MR-PWI data might be a predictor of full MCA-M1 recanalization in patients treated with IV thrombolysis. 24 Nevertheless, PET studies have shown that there are differences regarding the stages of compensation throughout the whole area that is generally defined as ischemic penumbra by the PWI-DWI mismatch criterion. 25 Until now, these regional differences are not taken into account in most studies when analyzing the penumbra and only minor attention has been devoted to the distribution of perfusion impairment rather than to the mere severity measured by absolute or relative values in perfusion parameter maps.…”
Section: Discussionmentioning
confidence: 99%